Efficacy and safety of warfarin in dialysis patients with atrial fibrillation: A systematic review and meta-analysis - Surapon Nochaiwong (2018)
Objective: To systematically review and meta-analyse the riskbenefit ratio of warfarin users compared with non-warfarin users in patients with atrial fibrillation (AF), who are undergoing dialysis. Methods: We searched PubMed/MEDLINE, EMBASE, SCOPUS, Web of Science, Cochrane Library, grey literature, conference proceedings, trial registrations and also did handsearch. Cohort studies without language restrictions were included. Two investigators independently conducted a full abstraction of data, risk of bias and graded evidence. Effect estimates were pooled using random-effect models. Main outcome measure: All-cause mortality, total stroke/thromboembolism and bleeding complications. Results: 14 studies included 37 349 dialysis patients with AF, of whom 12 529 (33.5%) were warfarin users. For all-cause mortality: adjusted HR=0.99 (95% CI 0.89 to 1.10; p=0.825), unadjusted risk ratio (RR) =1.00 (95% CI 0.96 to 1.04; p=0.847). For stroke/ thromboembolism: adjusted HR=1.06 (95% CI 0.82 to 1.36; p=0.676), unadjusted incidence rate ratio (IRR) =1.23 (95% CI 0.94 to 1.61; p=0.133). For ischaemic stroke/transient ischaemic attack, adjusted HR=0.91 (95% CI 0.57 to 1.45; p=0.698), unadjusted IRR=1.16 (95% CI 0.84 to 1.62; p=0.370). For haemorrhagic stroke, adjusted HR=1.60 (95% CI 0.91 to 2.81; p=0.100), unadjusted IRR=1.48 (95% CI 0.92 to 2.36; p=0.102). Major bleeding was increased among warfarin users; adjusted HR=1.35 (95% CI 1.11 to 1.64; p=0.003) and unadjusted IRR=1.22 (95% CI 1.07 to 1.40; p=0.003). Conclusions: Among dialysis patients with AF, warfarin therapy was not associated with mortality and stroke/thromboembolism, but significantly increased the risk of major bleeding. More rigorous studies are essential to demonstrate the effect of warfarin for stroke prophylaxis in dialysis patients with AF.